2022
DOI: 10.30872/mulrev.v7i2.905
|View full text |Cite
|
Sign up to set email alerts
|

Are there International Labour Standards? Case of Migrant Workers’ Exploitation in Italy

Abstract: The increasingly fierce competition in the world of work has an impact on people getting jobs. The condition makes most people become migrants by traveling to other countries to find a job for a decent life in the future. However, the work that migrant workers get is often not as expected, so the rights of migrants are often not fulfilled. The amount of violence in the world of work and the non-fulfillment of the rights of migrant workers in Italy is an act that violates human rights. Therefore, the authors wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…According to the reports from Gunawan and Rizki (2022), it could be concluded that government still does not have solid categorization of disability. This is represented on the data collection methods by the government, where they used three different measurements of disability in Village Potential Survey (Pendataan Potensi Desa), National Survey of Working Forces (Survei Angkatan Kerja Nasional), and National Survey of Social and Economics (Survei Sosial Ekonomi Nasional).…”
Section: Structural Factor and Disability Identity Developmentmentioning
confidence: 99%
“…According to the reports from Gunawan and Rizki (2022), it could be concluded that government still does not have solid categorization of disability. This is represented on the data collection methods by the government, where they used three different measurements of disability in Village Potential Survey (Pendataan Potensi Desa), National Survey of Working Forces (Survei Angkatan Kerja Nasional), and National Survey of Social and Economics (Survei Sosial Ekonomi Nasional).…”
Section: Structural Factor and Disability Identity Developmentmentioning
confidence: 99%